Coenoflora of the Crambe tataria Sebeók in Western Kazakhstan (Experimental biology, 2020)
There are four species of the genus Crambe grow on the territory of Kazakhstan, one is Grambe tаtaria Sebeók which is listed in the Red Book of Kazakhstan as a rare and endangered species. In Kazakhstan the natural habitat of Crambe tataria is the chalk areas of the western part of the country (Aktobe region). Knowledge of the current state of local populations of this rare species and their ecologo-coenotic features are necessary in order to work out the measures for its conservation. In this connection, a study of the coenoflora of Crambe tataria  was carried out in Western Kazakhstan. As a result of the study, it was found that the coenoflora of Crambe tataria in Western Kazakhstan includes 141 species belonging to 33 families and 95 genera. The leading families are: Asteraceae (34), Brassicaceae (17), Fabaceae (10), Poaceae (9 species). The leading genera are Allium, Astragalus, Artemisia, Centaurea, Achillea. The composition of the coenoflora reflects the ecological conditions of calciferous and partly clay habitats in which populations of Crambe tataria are formed. Anthropogenic disturbance of the coenoflora is expressed in a fairly large number of weed species (11 species or 7.9 %).Key words: Crambe tаtaria, coenopopulation, Western Kazakhstan, systematic structure, ecological and coenotic groups.